2014
DOI: 10.4103/2229-516x.125675
|View full text |Cite
|
Sign up to set email alerts
|

The attitudes and perceptions of medical students towards basic science subjects during their clinical years: A cross-sectional survey

Abstract: Introduction:In the conventional system of medical education, basic subjects are taught in the 1st year with least interdisciplinary interaction. The objective of this study was to explore the students’ perception about content, need and application of basic science subjects during the clinical years of their medical education.Materials and Methods:A total of 300 questionnaires were distributed among students randomly after taking their written consent for participation in the study. About 265 completely fille… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
51
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 18 publications
(26 reference statements)
11
51
0
Order By: Relevance
“…To support these finding, one study found that intrinsic motivation (intrinsic goal orientation) significantly associated with deep strategy use [7]. In line with other previous findings [7,33], this is typical of 1 st year medical students who are trying many ways of dealing with the perceived overloaded and difficult basic medical subjects [21][22][23]34]. …”
Section: Motivation and Learning Strategiessupporting
confidence: 66%
“…To support these finding, one study found that intrinsic motivation (intrinsic goal orientation) significantly associated with deep strategy use [7]. In line with other previous findings [7,33], this is typical of 1 st year medical students who are trying many ways of dealing with the perceived overloaded and difficult basic medical subjects [21][22][23]34]. …”
Section: Motivation and Learning Strategiessupporting
confidence: 66%
“…Our students have voiced a similar opinion as few studies undertaken in other medical colleges in the India covering some aspects of the preclinical curriculum [6,7]. This study is important as it reflects the view of the students on the questions based on the comprehensive list of ongoing practical training in preclinical departments.…”
Section: Discussionmentioning
confidence: 88%
“…This descriptive, cross-sectional study was conducted at Mysore Medical College & Research Institute, Mysore using a predesigned questionnaire which was duly modified to suit the local situation and keeping the Medical Council of India vision 2015 document in mind [6][7][8][9][10]. First part (Question No.1-12) of the questionnaire related to importance of basic science subjects, time duration, vastness, clinical applicability, recall aspects, which were to be answered on a 5 point Likert scale (strongly disagree, disagree, neutral, agree, strongly agree).…”
Section: Methodsmentioning
confidence: 99%
“…There is also a need to move beyond the how, to when and what to teach in anatomy. Many studies have shared the view that the anatomy syllabus taught is voluminous and unnecessary [19,20]. A minimum working knowledge of anatomy is required which allows a doctor to practice safely and to communicate with other medical professionals and patients effectively [21].…”
Section: Discussionmentioning
confidence: 99%